The Effects of Trimetazidine on Lipid Peroxidation in Patients with End-Stage Renal Disease - Agen, Bilge; Celiker, Huseyin; Dogukan, Ayhan; Ilhan, Necip (Prous Science, Sau-Thomson Reuters, 2008)
It is known that the increase in levels of free oxygen radicals is important in the development of complications related to end-stage renal disease (ESRD) This stuck investigated plasma malondialdehyde (MDA) levels as a marker of lipid peroxidation (LPO), and the effects of trimetazidine (TMZ), which is known to have antioxidiant activity, on LPO. The study registered 16 hemodialysis patients, 16 continuous ambulatory peritoneal dialysis (CAPD) patients and 24 healthy individuals. The patients were given TMZ 60 mg/day divided into three doses for 6 months. Plasma AIDA levels were significantly higher in both patient groups before the treatment compared to the controls (P < 0.001). MDA levels after treatment with TMZ declined (from 1.94 +/- 0.58 nmol/ml to 0.73 +/- 0.35 nmol/ml; P < 0.001) in the hemodialysis group and (from 1.51 +/- 0.32 nmol/ml to 0.50 +/- 0.17 nmol/ml; P < 0.001) in the CAPD group. In this study it was found that oxidative stress markedly increased in both dialysis groups, and TMZ treatment reduced the increased production of oxygen radicals. We believe that TMZ can pi-event the effects of increased oxidative stress through its systemic antioxidant effects and may also be useful for the treatment of cardiovascular complications, the major cause of mortality in ESRD.
Keywords: Trimetazidine; Malondialdehyde; End-stage renal disease